2016
DOI: 10.3139/120.110941
|View full text |Cite
|
Sign up to set email alerts
|

Salt fog corrosion behavior of friction stir welded AA2014-T651 aluminum alloy

Abstract: High strength aluminum alloys of type AA2014 are used in aerospace applications. This alloy is considered unweldable using fusion welding processes. Friction stir welding being a solid state process has been proved to be a suitable process for obtaining sound welds of these materials. In the current study, 8 mm thick rolled AA2014-T651 aluminum alloy plates were joined using friction stir welding. The corrosion behavior of base material and friction stir welds was investigated using the salt fog test (ASTM B11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…For example, Thamilarasan et al researched the salt fog corrosion behavior of friction-stir-welded AA2014-T651 aluminum alloy. The results showed that the corrosion resistance of the welds and parent material in the basic solution was better than that in acidic and neutral solutions [ 24 ]. Qin et al investigated the corrosion behavior of friction-stir-welded 2A14-T6 aluminum alloy in immersion exfoliation corrosion (EXCO) solution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Thamilarasan et al researched the salt fog corrosion behavior of friction-stir-welded AA2014-T651 aluminum alloy. The results showed that the corrosion resistance of the welds and parent material in the basic solution was better than that in acidic and neutral solutions [ 24 ]. Qin et al investigated the corrosion behavior of friction-stir-welded 2A14-T6 aluminum alloy in immersion exfoliation corrosion (EXCO) solution.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive re-views carried out by Mishra and Ma [3] and Nandan et al [4] revealed sizable amount of information on the effects of process parameters, variations in microstructures, and structure-property correlations. More recently, there have been a number of reports [5][6][7][8][9][10] highlighting the changes in microstructures, dissolution and coarsening of strengthening precipitates in the weld nugget and formation of wide precipitatefree zones in the heat affected zone due to the plastic defor-mation and frictional heat associated with FSW. Also, several investigators studied the corrosion behavior of friction stir welded aluminum alloys [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%